Exploring the Impact of Electronic Word of Mouth, Consum-er Experience, and Trust on OVO Application Adoption: A Case Study of Medan Petisah Community - Elyna Shandra; Diantan Reivaldo; Purba, Lenta Friska; Chaniago, Sabaruddin (Journal of Business Integration Competitive, 2025)
The rise of financial technology has transformed money management, shifting from traditional methods to digital solutions, with e-wallets like DANA, GoPay, ShopeePay, and OVO becoming widely used, especially among younger people in Medan City. OVO, a popular e-wallet since its 2017 launch, initially offered numerous features and a broad network of partnerships, but its usage has recently declined due to increasing competition. This decline is attributed to factors such as negative electronic word-of-mouth (E-WOM), technical glitches, customer service issues, and concerns over security and transparency. The study, focused on OVO users in Medan Petisah, used purposive sampling to select 96 respondents based on availability and research criteria, with the sample size calculated using the Lemeshow formula, appropriate for unknown populations. The findings reveal that E-WOM, consumer experience, and trust significantly influence the decision to use OVO, with the combination of these factors playing a key role in driving adoption, emphasizing the importance of user feedback, personal experience, and trust in shaping usage decisions. From a managerial perspective, this implies that OVO must focus on improving customer service, addressing technical issues, and building stronger trust through enhanced security measures. Additionally, fostering positive E-WOM and providing better consumer experiences are crucial to regaining market share and encouraging more frequent usage of the app.